2006
DOI: 10.1186/1897-4287-4-3-136
|View full text |Cite
|
Sign up to set email alerts
|

Familial Aggregation of Non-Hodgkin's Lymphoma (NHL). A Case Report

Abstract: A family is reported in which three male siblings of Asian descent developed non-Hodgkin's lymphoma (NHL). Case 1 was diagnosed with indolent follicular lymphoma stage IIIA at age 45. Case 2 presented with large B-cell lymphoma stage IIB at age 56. Chromosomal investigation of the peripheral blood did not show abnormalities. Chemotherapy induced a complete remission. However, after a period of nearly ten years he developed acute myeloid leukaemia. Case 3 developed large B-cell lymphoma stage IVA at age 52. Cyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
(18 reference statements)
0
5
0
Order By: Relevance
“…Familial clustering of NHL has been described, including a report of 38 families with multiple cases of NHL [129]. A large case–control study (the Scandinavian Lymphoma Etiology [SCALE] study) undertaken in Denmark and Sweden found a history of hematopoietic disorders among any first-degree relatives to be a significant risk factor for all NHLs (odds ratio: 1.8; 95% CI: 1.2–2.5) [130].…”
Section: Genetic and Epigenetic Factors And Ocular Adnexal Nhlmentioning
confidence: 99%
“…Familial clustering of NHL has been described, including a report of 38 families with multiple cases of NHL [129]. A large case–control study (the Scandinavian Lymphoma Etiology [SCALE] study) undertaken in Denmark and Sweden found a history of hematopoietic disorders among any first-degree relatives to be a significant risk factor for all NHLs (odds ratio: 1.8; 95% CI: 1.2–2.5) [130].…”
Section: Genetic and Epigenetic Factors And Ocular Adnexal Nhlmentioning
confidence: 99%
“…In 2006, Loves et al. reported a family in which three male siblings developed NHL [ 6 ]. Those three siblings had different pathological types of lymphoma and were diagnosed at ages 45, 56, and 52 years.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature review, we found multiple cases of siblings with NHL (some are as case reports and others included in crosssectional and other research studies). In 2006, Loves et al reported a family in which three male siblings developed NHL [6]. Those three siblings had different pathological Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the literature review, we found multiple cases of siblings with NHL (some are as case reports and others included in cross-sectional and other research studies). In 2006 Loves et al reported a family in which three male siblings developed NHL (7). Those three siblings had different pathological types of lymphoma and were diagnosed at ages (45,56,52).…”
Section: Discussionmentioning
confidence: 99%